Cross-cultural adaptation and validation of the Jefferson Scale of Patient's Perceptions of Physician Empathy (JSPPPE) for the Portuguese population - Domingues, Ana Catarina (2019)
Objectives: To translate the Jefferson Scale of Patient Perceptions of Physician Empathy (JSPPPE) to the European Portuguese spoken language and to verify its reliability and validity. Methods: Cultural adaptation and linguistic translation from English to European Portuguese, revision of translations, semantics equivalence, and grammar correction of the Portuguese wording were made. Readability of the Portuguese version was verified and the analysis of internal consistency and correlation with the subscale “physician–patient relationship” of the Portuguese version of European Task Force on Patient Evaluation of General Practice Care Scale (EuroPEP) were made. Reliability was tested by intertemporal stability and internal consistency. Validity of criteria and construction was also verified. Results: The Portuguese translation was adapted to the 8th or 9th grade level, easy to understand. There was the need to change the visual appearance of the scale, answers below sentences. Interclass correlation coefficient for reliability varied between 0.737 and 1.000 and Cronbach’s α between 0.806 and 0.877. Validity was verified by comparing values of socio-demographic variables for JSPPPE index and for EuroPEP with no differences. Correlation values between the total score and its five items varied from 0.806 to 0.934. Criterion validity against EuroPEP had a correlation of 0.831. Conclusion: This study fulfilled the necessary steps to translate, verify the validity and the reliability of the Portuguese version of the JSPPPE, with minimum layout alteration. All five items were maintained. The authors recommend the use of the JSPPPE in research and clinical practice.